2018
DOI: 10.1515/ijamh-2017-0141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of communication skills based group counseling on mothers’ sex dialogue with their adolescent daughters

Abstract: Background Sex dialogue is one of the most critical and challenging topics between mothers and adolescents. The knowledge and skills of mothers in sex dialogue with their daughters are essential. The purpose of this study is to determine the effect of group counseling based on communication skills on mothers through their sex dialogue with their daughters. Methods A randomized controlled field trial was conducted on 168 couples of mothers and their daughters selected by the stratified matching method and rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The results indicated that both parents and students considered sex education to be of high importance, and in addition, parents showed a special interest in teaching the basic principles of rights and protection of children and adolescents, as well as health and biological principles (34). Ziaei and Gorji (2018) in their study have shown that the use of interventional counseling program of communication skills and sexual health signi cantly increases the frequency of mother-daughter dialogue on sex compared to the control group (35). The results of a study by Fatehi Pouladi et al in 2019 with the aim of determining the effectiveness of group education on participation, attitude and awareness of mothers in child sex education showed a signi cant difference in knowledge, attitude and participation of mothers after training in the intervention and control groups, indicating that after education, the mothers were more involved in sexual education of the child (36).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that both parents and students considered sex education to be of high importance, and in addition, parents showed a special interest in teaching the basic principles of rights and protection of children and adolescents, as well as health and biological principles (34). Ziaei and Gorji (2018) in their study have shown that the use of interventional counseling program of communication skills and sexual health signi cantly increases the frequency of mother-daughter dialogue on sex compared to the control group (35). The results of a study by Fatehi Pouladi et al in 2019 with the aim of determining the effectiveness of group education on participation, attitude and awareness of mothers in child sex education showed a signi cant difference in knowledge, attitude and participation of mothers after training in the intervention and control groups, indicating that after education, the mothers were more involved in sexual education of the child (36).…”
Section: Discussionmentioning
confidence: 99%